Flexible and conductive titanium carbide–carbon nanofibers for high-performance glucose biosensing. (10th August 2018) - Guo, Qiaohui; Liu, Lijuan; Wu, Tingting; Wang, Qingqing; Wang, Honghong; Liang, Jianyu; Chen, Shuiliang
Abstract: The demand for developing novel materials to construct high-performance enzymatic glucose biosensors is rising, due to enzyme tend to denaturation and leaking from electrodes. Titanium carbide (TiC), as one of the most important transition metal carbides, exhibits good chemical stability and electrical conductivity, and electrocatalytic activity resembling that of metals, but is much cheaper. In this work, TiC–carbon nanofibers (CNFs) film (TCNFs) is synthesized by a one-step synthesis technique, which could maintain its structural integrity with robust adhesion, and could be produce in large quantity. Uniform TiC nanoparticles (NPs) are firmly embedded into the CNFs matrix. When TCNFs is applied for glucose oxidase (GOD) immobilization and biosensing, flexible TCNFs with good conductivity and porous nature facilitates electron transfer and GOD loading. The as-prepared glucose biosensor possesses excellent sensing performance, which exhibits a wide linear range (0.013–10.5 mM, R 2  = 0.999), a low detection limit (3.7 μM, S/N = 3), satisfactory reproducibility, good selectivity and anti-interference ability. Simple synthetic method and excellent electrochemical performance make TCNFs promising as an ideal substrate to fabricate effective electrochemical biosensors. Highlights: A one-step synthesis technique for titanium carbide-carbon nanofibers (TCNFs). Uniform TiC nanoparticles firmly embedded into CNFs matrix. TCNFs showed a 3D porous structure. High-performance enzymatic-based glucose sensor was constructed.